Fishes from the Tusubres River basin, Pacific coast, Costa Rica: Checklist, identification key and photographic album - Angulo, Arturo [UNESP]; Molina-Arias, Alex; Murase, Atsunobu; Miyazaki, Yusuke; Bussing, William; López, Myrna (Pensoft Publishers, 2015)
A checklist of the fishes of the Tusubres River basin, Pacific coast of Costa Rica, compiled from field and museum surveys is herein presented. A total of 54 species, representing 47 genera and 27 families, were recorded. Peripheral species were dominant (64.8%), followed by secondary freshwater fishes (20.4%); primary freshwater fishes accounted only for 14.8% of the total fish diversity. Eleotridae (6 spp.), Gobiidae (6 spp.), Poeciliidae (5 spp.) and Characidae (4 spp.) were the most diverse. Two species (Caranx sexfasciatus, Carangidae; and Opisthonema libertate, Clupeidae) were new records for Costa Rican freshwaters, and two species (Gymnotus maculosus, Gymnotidae; and Lebiasina boruca, Lebiasinidae) was found to have expanded ranges. An identification key and a complete photographic album of all fish species recorded in the basin are presented. The results of this investigation provide a framework for future studies on biogeography, ecology and conservation on fishes from this area.
Keywords: Central America; Ichthyofauna; Inventory; New records